Analisis Pengaruh Nilai Tukar, Tingkat Suku Bunga, dan Inflasi Terhadap Indeks Harga Saham (Studi Kasus pada Perusahaan Properti yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2021) - Fikiruddin, Ahmad; Sudaryanti, Dwiyani; Hariri, Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2024)
The aim of this research is to determine and analyze the influence of exchange rates, interest rates and inflation on the Property Sector Stock Price Index listed on the Indonesia Stock Exchange for the 2018-2021 period. This research is correlational research using a quantitative approach. The data used in this research is secondary data obtained from the official website of the Indonesia Stock Exchange (BEI) and the official website of Bank Indonesia (BI). The sample used in this research is monthly data on the property sector share price index for the 2018-2021 period, totaling 48 pieces of data. The sampling technique uses a purposive sampling method. The data analysis used is multiple linear regression analysis using SPSS. The research results show that simultaneously the exchange rate, interest rates and inflation have a significant effect on the property sector stock price index. Partially, the exchange rate has a negative effect on the property sector stock price index, while interest rates and inflation do not have a significant effect on the property sector stock price index.Keywords: Exchange rate, interest rate, inflation, property sector stock price index.